First results of the French OCTOPUS survey among festival attendees: a latent class analysis - Marion Istvan; Vincent Bresdin; Marie Mainguy; Pauline Laigo; Marie Grall-Bronnec; Vincent Eudeline; Jean-Emmanuel Guillet; Manon Guillo; Laurent Babonnaud; Pascale Jolliet; Benoit Schreck; Caroline Victorri-Vigneau (BMC, 2023)
Abstract Background Illicit substance use has constantly evolved over the years, particularly in the party scene. Monitoring these changes is essential to adapt harm reduction strategies. The OCTOPUS survey was implemented to enhance knowledge on drug use at music festivals. The objective of the work presented here was to describe drug use and to characterize profiles of substance use in music festival attendees. Methods OCTOPUS was a cross-sectional survey carried out during 13 various music festivals (dub, eclectic and electronic music) in the Loire-Atlantique department (France) from July 2017 to July 2018. Participants were festival attendees. Data were collected by trained research staff using a face-to-face structured interview. We analysed the use of illicit drugs in the last 12 months to describe the prevalence of use and to characterize the profile of substance use using a latent class analysis. Results In total, 383 festival attendees were included. Of 314 (82%) participants who reported drug use, the most reported drugs were cannabis, ecstasy/MDMA and cocaine. We identified two profiles of drug use: (i) a "no/low polysubstance use" profile mainly characterized by the use of "classic" stimulants (ecstasy/MDMA, cocaine) and (ii) "moderate/extensive polysubstance use", with high probabilities of "classic" stimulants use and especially other drugs reported: speed, ketamine, new psychoactive substances (NPSs). Conclusion We observed frequent polysubstance use in festival attendees. Harm reduction should be targeted at the increased risk of toxicity linked to polysubstance use, and the reduction in harm caused by particular drugs (ketamine, NPS, speed) could be further strengthened.